Framing Prabowo's 'Gemoy' Campaign: National and International Media Perspectives - Esa Rezki Habibillah; Didik Hariyanto (Universitas Telkom, 2026)
The “Prabowo Gemoy” campaign has become a prominent political communication innovation in Indonesia, particularly in targeting younger voters through humorous, expressive, and highly visual content. This study analyzes how two media outlets, Kumparan (as national media) and BBC News (as international media), frame the campaign using Robert M. Entman’s framing analysis model. A qualitative media text analysis method was employed to examine four key elements of framing: defining problems, diagnosing causes, making moral judgments, and suggesting remedies. The results indicate that Kumparan frames the campaign as a modern and emotionally resonant strategy to connect with Gen Z and millennial voters, depicting it as a breakthrough in digital political marketing. Conversely, BBC News frames the campaign critically, highlighting the risks of image rebranding and the potential whitewashing of Prabowo's controversial human rights record. These divergent frames reflect the cultural and institutional differences between the media outlets. This study concludes that media not only report political events but actively shape public perception and political discourse through strategic framing, which plays a crucial role in constructing the image of political figures.